Les apports de la gouvernance adaptative pour analyser les enjeux d’une mise en œuvre effective de la Trame Verte et Bleue. L’exemple du PNR des Volcans d’Auvergne - Valérie Angeon; Armelle Caron; Cécile Birard; Patrice Cayre; Philippe Chambon; Arnaud Larade; Ludovic Méasson; Claire Planchat (Développement Durable et Territoires)
The Green and Blue infrastructure (Trame verte et bleue –TVB) is a new conservation policy tool based on the notions of ecological network and corridor. The introduction of this new instrument through the French Grenelle environment commitments brings about some change in the spatial strategy of the conservation policy. Beyond the identification of priority conservation areas, ecological planning of all the territory is concerned. The TVB’s implementation process establishes the connection of multi and nested decisional and action levels. It thus creates specific situations of complexity and uncertainty that require innovation and perpetual change of governance. The study of the Auvergne region case through the adaptive governance analytical framework highlights the potential fruitful role of Regional nature parks in such dynamics of change and learning.